Návrh změn konceptu motivačního systému ve vybraném podniku - Vlachová, Šarlota (Vysoké učení technické v Brně. Fakulta podnikatelská, 2024)
Bakalářská práce se zabývá řízením lidských zdrojů. Hlavním cílem této práce je navrhnout změny v motivačním systému daného podniku, které podpoří rozvoj v této oblasti. Teoretická část se věnuje výkladu, který je podkladem pro tvorbu analytické části a pro vlastní návrhy na zlepšení motivace zaměstnanců, a jejich následné zvýšené výkonnosti a spokojenosti. Problémy byly identifikovány prostřednictvím pohovorů s vedením podniku a dotazníkovým šetřením. Na základě zjištěných nedostatků bylo následně přikročeno k návrhům v dané oblasti.

This Bachelor’s thesis deals with human resourcing management. Main goal of this thesis is to propose changes in the motivational system of the company, which supports development in this area. Theoretical part is devoted to the interpretation, which is the basis for creation of the analytical part and their own proposals to improve employee motivation and their subsequent effectiveness and satisfaction. The problems were identified through interviews with the company's management and a questionnaire survey. There were made several proposals in this area due to insufficient results.
Proposal for Changes of Motivational System in a Selected Company.
Keywords: lidské zdroje; odměňování zaměstnanců; mzda; zaměstnanecké benefity; motivace; motivační systém; human resources; rewarding employees; salary; employee benefits; motivation; motivation system